A smart devices based secondary prevention program for cerebrovascular disease patients - Motolese, Francesco; Capone, Fioravante; Magliozzi, Alessandro; Vico, Carlo; Iaccarino, Gianmarco; Falato, Emma; Pilato, Fabio; Di Lazzaro, Vincenzo (Frontiers in Neurology, 2023)
Background: Commercially available health devices are gaining momentum and represent a great opportunity for monitoring patients for prolonged periods. This study aimed at testing the feasibility of a smart device-based secondary prevention program in a cohort of patients with cryptogenic stroke. Methods: In this proof-of-principle study, patients with non-disabling ischemic stroke and TIA in the subacute phase were provided with a smartwatch and smart devices to monitor several parameters – i.e., oxygen saturation, blood pressure, steps a day, heart rate and heart rate variability - for a 4-week period (watch group). This group was compared with a standard-of-care group. Our primary endpoint was the compliance with the use of smart devices that was evaluated as the number of measures performed during the observation period. Results: In total, 161 patients were recruited, 87 in the WATCH group and 74 in the control group. In the WATCH group, more than 90% of patients recorded the ECG at least once a day. In total, 5335 ECGs were recorded during the study. The median blood pressure value was 132/78 mmHg and the median oxygen saturation value was 97 %. From a clinical standpoint, although not statistically significant, nine atrial fibrillation episodes (10.3%) in the WATCH group vs 3 (4%) in the control group were detected. Conclusion: Our study suggests that prevention programs for cerebrovascular disease may benefit from the implementation of new technologies.